Assessing The Impact of Accounting Information Systems on Internal Control of Micro Credit Services at Banking Institutions in Bandung - Irfan Usmaya; Siti Mialasmaya; Jimmy Rusjiana; Sana Sholihah; R. Deni Purana (Informatics Management, Engineering and Information System Journal, 2026)
This study explores the impact of the accounting information system on credit granting and its effect on internal control over micro credit distribution. The main aim is to understand the relationship between these factors. To accomplish this, the research employs various methods like observation, interviews, and literature reviews. The analysis uses the Pearson correlation coefficient, demonstrating a strong relationship between the independent and dependent variables. The findings reveal that a significant portion of the variation in internal control over micro credit granting relates to problematic credits, while some influences come from factors not examined in this research. The emerging issues include ineffective credit analysis that leads to insufficient understanding of customer businesses, along with the misuse of loans by debtors, which negatively impacts bank profits. Recommendations for micro credit services at banking institutions in Bandung highlight the necessity for more assertive loan collection practices and increased vigilance in applying credit assessment frameworks such as the 5C and 7P models. This study brings forward the novelty of linking the effectiveness of the accounting information system directly to the internal control over micro credit distribution. By highlighting the specific relationship between these elements, it sheds light on how improved credit analysis can prevent debtor misuse and enhance bank profitability. This focus not only addresses existing gaps in understanding within the industry but also offers practical recommendations tailored for micro credit services at banking institutions in Bandung. The implications of these findings suggest that a more robust framework for credit assessment, particularly the application of the 5C and 7P models, could significantly improve the lending process. This innovative approach fosters a deeper understanding of customer behavior and financial practices, ultimately contributing to more sustainable lending strategies.